Asymptotic Expansion for the Distribution and Density Functions of the Quadratic Form of a Stationary Gaussian Process in the Large Deviation Cramer Zone - Saulis, L. (Nonlinear Analysis: Modelling and Control, 2001)
The work considers the asymptomic expansions in the large deviation Cramer zone for the distribution and its density functions of the quadratic form a stationary Gaussian sequence. To this end the general authors lemma [1], [3] for an arbitrary random variable with regular behavior of its cumulants is used.